1990
DOI: 10.1095/biolreprod43.6.913
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation of Bovine Theca and Granulosa Cells into Small and Large Luteal-like Cells: Morphological and Functional Characteristics1

Abstract: This study was undertaken to investigate whether bovine granulosa and theca interna cells could be luteinized in vitro into luteal-like cells. Granulosa and theca cells were cultured for 9 days in the presence of forskolin (10 microM), insulin (2 micrograms/ml), insulin-like growth factor I (100 ng/ml), or a combination of these agents. During the first day of culture, granulosa and theca cells secreted estradiol and androstenedione, respectively; progesterone rose only after 3-5 days in culture and reached a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 0 publications
10
74
0
1
Order By: Relevance
“…In vitro, granulosa cells harvested from follicles always spontaneously luteinize (Meidan et al 1990). However, in cultured bovine granulosa cells harvested from small bovine antral follicles, the addition of low dose of FSH maintains follicle characteristics by stimulating E 2 and CYP19A1 for several days (Gutierrez et al 1997, Silva & Price 2002, Sahmi et al 2004) and appears to counteract the process of luteinization by inhibiting STAR mRNA expression (Zheng et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, granulosa cells harvested from follicles always spontaneously luteinize (Meidan et al 1990). However, in cultured bovine granulosa cells harvested from small bovine antral follicles, the addition of low dose of FSH maintains follicle characteristics by stimulating E 2 and CYP19A1 for several days (Gutierrez et al 1997, Silva & Price 2002, Sahmi et al 2004) and appears to counteract the process of luteinization by inhibiting STAR mRNA expression (Zheng et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Follicles are highly dependent on gonadotropins to achieve ovulatory size (Fortune and Hilbert 1986). Starting when they are approximately 4 mm diameter, the expression of P450 aromatase increases and follicle growth ceases if FSH is suppressed (Meidan et al 1990;Xu et al 1995a). After reaching approximately 8 mm diameter, bovine follicles express LH receptors on the GC (Xu et al 1995a).…”
mentioning
confidence: 99%
“…Based on these data, one could assume that bovine granulosa cells obtained from small antral follicles can differentiate into large luteal-like cells during culture in vitro, and that the cultured granulosa cells can be used as a model of large luteal cells. Meidan et al [8] showed that bovine granulosa cells obtained from preovulatory follicles differentiated into large luteal-like cells during culture in the presence of insulin plus forskolin. In the present study, granulosa cells obtained from small antral follicles could also be luteinized when they were incubated with insulin plus forskolin.…”
Section: Discussionmentioning
confidence: 99%